The Horn of Africa at the end of the Pleistocene (75-12ka) in its macroregional context. - (:unkn) unknown (My University, 2020)
The archaeological data available in Africa for the period ranging from 75 to 12 ka are generally attributed to two major Palaeolithic phases: the Middle Stone Age (MSA) and the Later Stone Age (LSA). This timeframe corresponds to the last glacial period the Earth experienced, characterised by high climatic variability and a general trend towards more arid conditions (lower temperatures and precipitation) culminating in Marine Isotope Stage (MIS) 2, also referred as the Big Dry (ca. 29-15 ka) before a shift to more humid conditions (African Humid Period). In this paper, we review current archaeological evidence in the Horn of Africa between 75 and 12 ka. We first discuss this evidence in light of palaeoenvironmental data and in particular with regard to the potential impact of the Big Dry on human occupation in the region. We then discuss the place of the Horn of Africa in a wider macro-regional context and evaluate potential links with neighbouring regions.
Keywords: African Research